Peningkatan Kandungan Pigmen Fotosintesis Ginseng Jawa (Talinum paniculatum Gaertn.) Menggunakan Asam Salisilat - Arif Yachya; Suparman; Ekiq Nouval Zaki; Marnitha; Awalul Fatiqin (Universitas PGRI Silampari, 2024)
This study was conducted to ascertain the impact of applying various concentrations of exogenous salicylic acid (AS) and its application durations on Talinum paniculatum`s chlorophyll content. This study used a complete randomized design of 2 factors, such us various concentrations (e.g., 0, 25, 50, 100, and 200 µM) and application durations (e.g., 1 and 2 weeks) of AS with three replications in each treatment group. Elicitation was performed on stem cuttings of T. paniculatum aged 41 days after planting where the cuttings already had enough leaves. Data analysis with variant testing and continued with Tukey`s test at the level of 5%. The results of the variant test showed elicitation with AS had a significant effect on the photosynthetic content of T. paniculatum leaves.